Analisis Semiotika pada Iklan Uber Edisi Boxes - Aryadillah Aryadillah (Cakrawala - Jurnal Humaniora, 2019)
In answering the current business competition, it is necessary to have a different promotion strategy from other competitors. In this case, it is not just to gain as much profit as possible, but also becomes an attraction for consumers if the company uses a media promotion strategy that is unique or different from the others, so there is a message that is created through communication semiotics. online motorcycle taxi phenomenon. Online motorcycle taxi services such as motorcycle taxi, grab and uber have stolen the attention of users of public transportation services. One of several online motorcycle taxi that is now stealing the attention is Uber. Through the Uber Edition Boxes advertisement, this online motorcycle taxi service has stolen the attention of other online motorcycle taxi users. Since it was published on November 1, 2017 through YouTube, this ad has been watched by 2,637,183 by cyber activists. This uniquely conceptualized ad carries the message "watch and see what will happen if our city is filled with people in unit boxes that fill city streets to the point of being ridiculous. Imagine that the people in this box are cars ... # ridetogether #unlockJakartas "